Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2022
DOI: 10.3389/fcvm.2022.886300
|View full text |Cite
|
Sign up to set email alerts
|

The role of post-translational modifications in driving abnormal cardiovascular complications at high altitude

Abstract: The high-altitude environment is characterized by hypobaric hypoxia, low temperatures, low humidity, and high radiation, which is a natural challenge for lowland residents entering. Previous studies have confirmed the acute and chronic effects of high altitude on the cardiovascular systems of lowlanders. Abnormal cardiovascular complications, including pulmonary edema, cardiac hypertrophy and pulmonary arterial hypertension were commonly explored. Effective evaluation of cardiovascular adaptive response in hig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 131 publications
(133 reference statements)
0
4
0
Order By: Relevance
“…40 Furthermore, protein lactylation has been associated with the regulation of environmental stress responses and organismal adaptation. 41 In plant physiology, a study has established a correlation between lactate and lactylation with the physiological response of maize root systems to drought stress. 42 Similarly, in animals enduring prolonged environmental stress, genes regulating lipid synthesis are downregulated, while those related to gluconeogenesis, 43 fatty acid oxidation, 43 and peroxisome proliferatoractivated receptor A (PPAR-A) target gene associated with lipolysis are upregulated.…”
Section: ■ Discussionmentioning
confidence: 99%
“…40 Furthermore, protein lactylation has been associated with the regulation of environmental stress responses and organismal adaptation. 41 In plant physiology, a study has established a correlation between lactate and lactylation with the physiological response of maize root systems to drought stress. 42 Similarly, in animals enduring prolonged environmental stress, genes regulating lipid synthesis are downregulated, while those related to gluconeogenesis, 43 fatty acid oxidation, 43 and peroxisome proliferatoractivated receptor A (PPAR-A) target gene associated with lipolysis are upregulated.…”
Section: ■ Discussionmentioning
confidence: 99%
“…I Na alterations have been implicated in HF. A HF study conducted on mice missing the expression of the Muscle Lim Protein (MLP) demonstrated a decreased of I Na density by post-translational reduction ( 35 , 36 ). This I Na reduction decreased the electrical conduction, favored re-entry, and contributed to inefficient synchronized conduction.…”
Section: Electrical Remodelingmentioning
confidence: 99%
“…One potential tool for studying how proteins are perturbed in the presence of PSNPs is lysine methylation. Methylation is a crucial post-translational modification in regulating diverse cellular processes and orchestrating complex biological functions. , Biologically, methylation is performed by a family of enzymes known as lysine methyltransferases . However, methylation can also be performed reductively using formaldehyde under mild conditions that do not alter the protein’s structure .…”
Section: Introductionmentioning
confidence: 99%